Odpowiedź :
Odpowiedź:
b) d) f)
3x-2y=1 2x-3y=0,7 0,4x-0,3y=-2
2x+y=0 x+4y=5,3 1,6x+1,5y=46
2x+y=0 x+4y=5,3 0,4x-0,3y=-2
y=0-2x x=5,3-4y 0,4x=-2+0,3y/:0,4
y=-2x x=-5+0,75y
3x-2y=1 1.6x+1.5y=46
3x-2*(-2x)=1 2x-3y=0,7 1,6*(-5+0,75y)+1,5y=46
3x+4x=1 2*(5,3-4y)-3y=0,7 -8+1,2y+1,5y=46
7x=1/:7 10,6-8y-3y=0,7 1,2y+1,5y=46+8
x=1/7 -8y-3y=0,7-10,6 2,7y=54/:2,7
-11y=-9,9/:(-11) y=20
y= 0,9
x=-5+0,75y
y=-2x x=5,3-4y x=-5+0,75*20
y=-2*1/7 x=5,3-4*0,9 x=-5+15
y=-2/7 x=5,3-3,6 x=10
x=1,7
Szczegółowe wyjaśnienie: